Efek Antibakteri Ekstrak Etanol Daun Pandan Wangi (Pandanus Amarylifolius) Terhadap Enterococcus Faecalis (In Vitro) - Aryadi Subrata; Valencia Lawrence (Jurnal Kedokteran Gigi Terpadu, 2021)
Background: Enterococcus faecalis is a bacterium that is commonly found in pulp necrosis and is difficult to get rid of, causing endodontic persistence. Irrigation materials which are often used these days still have some limitations that can lead to failure of root canal treatment. Pandanus amarylifolius leaf is an herbal ingredient that has several active compounds such as flavonoids, polyphenols, saponins, and alkaloids are known for having antibacterial effects which are expected to inhibit E. faecalis . Objective: To determine the antibacterial effect of ethanol extract of pandan wangi leaves on the growth of bacteria E. faecalis. Method: Experimental laboratory with well diffusion method. The ethanol extract of wangi pandan leaves was obtained by maceration method using 96% ethanol as a solvent. Aquades was used as a negative control, 0,2% chlorhexidine as a positive control, and the concentrations of ethanol extract of Pandan wangi leaves used were 6.25%, 12.5%, 25%, 50%, and 100%. Results: The ethanol extract of pandan wangi leaves had an antibacterial effect on the growth of E. faecalis. Extract concentrations of 6.25%, 12.5%, and 25%, don’t have inhibiton zone. Extract concentrations 50% and 100% had an average inhibition zone diameter of 11,400 ± 2,621 mm; The positive control shows the average inhibition zone of 16,094 ± 2,981 mm, while the negative control does not have an inhibition zone. Conclusion: Ethanol extract of pandan wangi leaves has an antibacterial effectivity against E. faecalis with the concentration 50% and 100%.